A sensitive and specific diagnostic test for hearing loss using a microdroplet PCR‐based approach and next generation sequencing123. Issue 1 (3rd December 2012) - Schrauwen, Isabelle; Sommen, Manou; Corneveaux, Jason J.; Reiman, Rebecca A.; Hackett, Nicole J.; Claes, Charlotte; Claes, Kathleen; Bitner‐Glindzicz, Maria; Coucke, Paul; Van Camp, Guy; Huentelman, Matthew J.
Abstract Implementing DNA diagnostics in clinical practice for extremely heterogeneous diseases such as hearing loss is challenging, especially when attempting to reach high sensitivity and specificity in a cost‐effective fashion. Next generation sequencing has enabled the development of such a test, but the most commonly used genomic target enrichment methods such as hybridization‐based capture suffer from restrictions. In this study, we have adopted a new flexible approach using microdroplet PCR‐based technology for target enrichment, in combination with massive parallel sequencing to develop a DNA diagnostic test for autosomal recessive hereditary hearing loss. This approach enabled us to identify the genetic basis of hearing loss in 9 of 24 patients, a success rate of 37.5%. Our method also proved to have high sensitivity and specificity. Currently, routine molecular genetic diagnostic testing for deafness is in most cases only performed for the GJB2 gene and a positive result is typically only obtained in 10–20% of deaf children. Individuals with mutations in GJB2 had already been excluded in our selected set of 24 patients. Therefore, we anticipate that our deafness test may lead to a genetic diagnosis in roughly 50% of unscreened autosomal recessive deafness cases. We propose that this diagnostic testing approach represents a significant improvement in clinical practice as a standard diagnostic tool for children with hearing loss. © 2012 Wiley Periodicals, Inc.